Adipocyte-induced transdifferentiation of osteoblasts and its potential role in age-related bone loss - Clabaut, Aline; Grare, Céline; Rolland-Valognes, Gaëlle; Letarouilly, Jean-Guillaume; Bourrier, Chantal; Andersen, Thomas L.; Sikjær, Tanja; Rejnmark, Lars; Ejersted, Charlotte; Pastoureau, Philippe; Hardouin, Pierre; Sabatini, Massimo; et al. (PloS one, 2021)
Our preliminary findings have lead us to propose bone marrow adipocyte secretions as new contributors to bone loss. Indeed, using a coculture model based on human bone marrow stromal cells, we previously showed that soluble factors secreted by adipocytes induced the conversion of osteoblasts towards an adipocyte-like phenotype. In this study, microarray gene expression profiling showed profound transcriptomic changes in osteoblasts following coculture and confirmed the enrichment of the adipocyte gene signature. Double immunofluorescence microscopic analyses demonstrated the coexpression of adipogenic and osteoblastic specific markers in individual cells, providing evidence for a transdifferentiation event. At the molecular level, this conversion was associated with upregulated expression levels of reprogramming genes and a decrease in the DNA methylation level. In line with these in vitro results, preliminary immunohistochemical analysis of bone sections revealed adipogenic marker expression in osteoblasts from elderly subjects. Altogether, these data suggest that osteoblast transdifferentiation could contribute to decreased bone mass upon ageing.